Efeitos tóxicos de surfactantes fitossanitários para o peixe mato grosso (Hyphessobrycon eques) - Carraschi, Silvia Patricia; Cubo, Patricia; Schiavetti, Barbara Lopes; Shiogiri, Natalia Sayuri; da Cruz, Claudinei; Pitelli, Robinson Antonio (Universidade Estadual de Maringa, 2011)
Toxic effects of phytosanitary surfactants for jewel tetra (Hyphessobrycon eques). Surfactants are amphipatic molecules that reduce the surface tension of water and make up the inert components of pesticide formulations. Thus, the objectives of this study were: to estimate the lethal concentration (LC(I)50;96h); classify and evaluate water quality during testing of the following surfactants: Agral[registered trademark], Aterbane[registered trademark]BR, Ag-bem[registered trademark], Energic[registered trademark], Fixade[registered trademark] and Gotafix[registered trademark] for jewel tetra (Hyphessobrycon eques); and the signs of intoxication in the animals. For this, the fish were acclimated for ten days in the bioassay room. The animals were exposed to the surfactants in an entirely randomized design with three replications. The LC(I)(50;96h) of surfactant Agral[registered trademark] was 3.29 mg L-1; Aterbane[registered trademark] BR 8.21 mg L-1; Energic[registered trademark] 2.34 mg L-1; Gotafix[registered trademark] 4.37 mg L-1; Fixade[registered trademark] 3.38 mg L-1; and Ag-bem[registered trademark] 34.95 mg L-1. The variables of water quality were unchanged. The fish showed an increase in the opercular beating after exposure; 4 and 24 hours, loss of gasping ability; 48 hours, slow opercular beating; and 72 and 96 hours later, recovery. The surfactants Energic[registered trademark], Agral[registered trademark], Gotafix[registered trademark], Aterbane[registered trademark] BR and Fixade[registered trademark] can be classified as moderately toxics, and Ag-Bem[registered trademark] as slightly toxic for H. eques; this organism shows similar intoxication signs for all surfactants.
Toxic effects of phytosanitary surfactants for jewel tetra (Hyphessobrycon eques).